2008
DOI: 10.2134/agronj2007.0377
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Effects on Onion Yield Under Drip and Furrow Irrigation

Abstract: Onion (Allium cepa L.) is a high cash value crop with a very shallow root system that is frequently irrigated and fertilized with high N rates to maximize yield. Converting from furrow-irrigated to drip-irrigated onion production may reduce N fertilizer needs, water inputs, and NO 3 -N leaching potential. Onion growth and N uptake, fresh yield, and residual soil NO 3 -N were determined under drip and furrow irrigation on a clay loam soil with N fertilizer rates from 0 to 224 kg N ha -1 . Onions were sampled bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 9 publications
3
39
1
1
Order By: Relevance
“…The excess of applied fertilizer or nutrient content in the soil does not produce benefits to plants or may even depress the uptake of nutrients as well as crop growth and yield (Lee, Lee 2014), either concerning nitrogen (Boyhan et al 2007;Halvorson et al 2008) or phosphorus and potassium (Laughlin 1989;Amin et al 2007;Boyhan et al 2007;Lee et al 2011). According to Lee et al (2011) no increase of bulb yield is achieved over the range of 7 to 42 mg/kg NO 3 -N content in the soil.…”
Section: Farming Practicesmentioning
confidence: 99%
“…The excess of applied fertilizer or nutrient content in the soil does not produce benefits to plants or may even depress the uptake of nutrients as well as crop growth and yield (Lee, Lee 2014), either concerning nitrogen (Boyhan et al 2007;Halvorson et al 2008) or phosphorus and potassium (Laughlin 1989;Amin et al 2007;Boyhan et al 2007;Lee et al 2011). According to Lee et al (2011) no increase of bulb yield is achieved over the range of 7 to 42 mg/kg NO 3 -N content in the soil.…”
Section: Farming Practicesmentioning
confidence: 99%
“…In most production regions onions have been traditionally irrigated with furrow irrigation, but susceptibility to wind drift, inconsistency and low efficiency are reported [75][76][77]. Drip irrigation is assumed to be more advantageous for onion production due to higher water distribution uniformity, reduced evaporation losses and deep percolation, but higher levels of management.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of NUE was associated with lower N utilization and higher onion yield. Studying N fertilizer effects on onion by illustrated that increasing N fertilizer led to reduce the NUE (Halvorson et al, 2008). NUE was reduced along with increasing N fertilizer at all plant densities (Figure 4).…”
Section: Nitrogen Use Efficiency (Nue)mentioning
confidence: 95%
“…Based on the effects of N rate × irrigation interactions on N losses, it can be concluded that an increase in irrigation amount at low levels of N rates led to no influence in N losses whereas, more N losses was found at high levels of N rates in the same conditions (Figure 3). Halvorson et al (2008) reported that soil nitrate generally increased with increasing N rate leading to the increase of nitrate leaching potential. They also described that drip system reduced soil nitrate leaching compared with furrow system.…”
Section: N Lossesmentioning
confidence: 99%